"دراسة مقارنة لتأثير اثنين من مواد التلميع على الاستقرار اللّوني للتيجان المؤقتة المصنعة من الراتنج الإكريلي ذاتي التصلب."(دراسة مخبرية) (Journal of Hama University, 2022)
Background and Aim of study: The most important factor affecting the aesthetic aspect is the color, whether the restoration is final or provisional Therefore, the discoloration of the provisional restoration can cause aesthetic problems that are critical for both the patient and the dentist. , this research aimed to compare the effect of two polishing materials on the color stability of provisional crowns Manufactured from self cure acrylic resin.Research Materials and Methods: The research sample consisted of 20 provisional crowns of bis-acryl material designed for an upper premolar that was prepared to receive a full ceramic crown. After obtaining the sample, the sample was divided into two main groups according to the type of polishing material used (aluminum oxide paste or diamond paste), after polishing, the color measurements of the research sample were made using a measuring device. Spectrophotometer Vita Easyshade®. After that, the crowns were immersed in a solution of coffee, distilled water, and stored in an incubator at a temperature (37+- 1)°C for 7 days, then colorimetric measurements were repeated and the color change ΔE was calculated for each of the research samples.The data were analyzed using Student's T-test for independent samples to study the significance of the differences in the mean amount of color change ∆E between the group of bis-acryl crowns were polished with diamond paste and the group of bis-acryl crowns, which were polished, with alumina paste in the research sample.Results: At the 95% confidence level, there were no statistically significant differences between aluminum oxide and diamond in the chromatic stability of the studied provisional restoration.Conclusions: Within the limitations of this study, there is no clear difference between the effect of the two materials of aluminum oxide paste and diamond paste in terms of the color stability of the provisional restoration material.
Keywords: Color stability, provisional restorations, polishing materials